Novel Use of the Buccal Fat Pad for Sinocutaneous Fistulae Closure and a Review of Reconstructive Options. (March 2022) - Pool, Christopher; Goyal, Neerav; Lighthall, Jessyka G.
Background: Sinocutaneous fistulae (SCF) are abnormal communications between the paranasal sinuses and the overlying skin. They may be difficult to manage due to facial geometry, scar contraction, and poor tissue vascularity. We describe a novel use of the buccal flap and review the literature to examine management options for this disease process. Methods: A PubMed/MEDLINE literature search was performed for studies published between January 1, 1950 and April 29, 2020 that describe management strategies for SCF. The clinical record, imaging, and operative reports were reviewed of the case in which the buccal fat flap was used in reconstruction. Results: A total of 359 articles were retrieved. After removing duplicate articles, non-English studies, animal studies, duplicate articles and studies that mentioned SCF without specific mention of management strategies, 51 articles were reviewed. Management paradigms throughout the articles include (1) removal of infection, (2) ensuring patency of sinus outflow tracts, (3) tensionless multilayered closure using well vascularized tissue, and (4) prevention or minimization of future risk factors for fistula formation. Conclusion: This article informs surgeons on reconstructive options for sinocutaneous fistulae including a novel description of the buccal fat flap.